Identifikasi Karakteristik Riset Interaksi Manusia dan Komputer di Indonesia: Alur, Metodologi, dan Arahnya di Masa Mendatang - Herti; Beny (LPPM Universitas Dinamika Bangsa, 2020)
Human and Computer Interaction is a multi-disciplinary field of study that focuses on designing computer technology that specifically looks at aspects of interaction between humans and computers. This research is a systematic literature review with the aim of investigating topics raised by Indonesian researchers in the field of Human-Computer Interaction and grouping research articles published based on HCI-Macro and HCI-Micro. This is done so that it is possible to know the impact on the outcomes of the research that has been done. Based on the grouping results obtained, as many as 95% of research articles fall into the HCI-Micro category. From these findings we propose ideas to next researchers to choose research topics in the field of Human and Computer Interaction that are able to have a greater impact in the HCI-Macro category.